Numerical analysis on the aerodynamic characteristics of SUV car model install with vortex generator - Muhammad Amirul Hakimin, Zainondin; Izuan Amin, Ishak; Mohd Fuad, Yasak; Arafat, Mohammad; Nor Atiqah, Zolpakar; Nurshafinaz, Mohd Maruai (Semarak Ilmu Publishing, 2025)
The investigation of automotive aerodynamics involves analysing several forces operating on a car while driving on the road, such as drag and lift forces. The flow separation at the vehicle’s rear end is one of the primary causes of aerodynamic drag for automobile vehicles. It is feasible to improve fuel efficiency by lowering the drag force. The study focuses on the influence of a vortex generator (VG) on the aerodynamics of a sport utility vehicle (SUV) car. The study aims to simulate fluid flow analysis for an SUV car that uses VG and without VG, as well as to assess the impact of a different configuration of VG and a varying number and fillet radius of VG. The number of VG are 3, 5, and 9. The different fillet radius of VG are 5, 10, and 15 mm. Using the Reynold-Averaged Navier Stokes Equation (RANS) in the numerical simulation, the Reynolds number at the computational domain is 1.1391 × 107 and 1.4808 × 107, which is determined by the height of the model and the freestream velocity. The results show that aerodynamic characteristics are significantly influenced by the number of VG and various size radius fillets of VG. From the result, 9 number of VG and 5 mm fillet radius obtained the lowest value of coefficient of drag, Cd compared with the others which is Cd = 0.3747 for 27.78 m/s and Cd = 0.5031 for 33.33 m/s, respectively. Furthermore, the analysis of flow structures suggested the locations of vortex formation and wake turbulence at the rear of the vehicle. In contrast, the 9 number of VG with a 5 mm radius fillet of VG emerged as the most suitable VG for this scenario, exhibiting a Cd value closest to the base model and the lowest Cd value.